Intestinal Ascariasis: The Unsuspected Cause of Acute Abdomen Detected on Ultrasonography - Moudgil, Sandeep; Singh, Lokesh; Behal, Manju (Archives of Clinical and Medical Case Reports, 2021)
Abstract not available in the source database.